PERBANDINGAN EFEKTIVITAS SIKAT GIGI KONVENSIONAL DENGAN SIKAT GIGI KHUSUS ORTODONTI TERHADAP PENURUNAN INDEKS PLAK PADA PEMAKAI PIRANTI ORTODONTI CEKAT MENGGUNAKAN METODE CHARTER - Ingrid Panbara; Kuswardani Susari Putri; Kosno Suprianto (Faculty of Dentistry Universitas Andalas, 2017)
accumulation of plaque. The most simple and effective way to control plaque is tooth brushing. Manual toothbrush which is straight, straight brush handle with the brush head and bristles panel is recommended by the healthy department of Indonesia. Orthodontic toothbrush is designed specifically to eliminate plaque around the brackets. Charter methods is recommended for patient using fixed orthodontic appliance. Purpose: To determine the effectiveness of conventional toothbrush and orthodontic toothbrush in reducing average plaque index patient using fixed orthodontic appliance with Charter method. Methods: The research method was experimental with pre and posttest design. The study subjects were 30 people who were divided into two groups, 15 people usedconventional toothbrushes and 15 people usedorthodontic toothbrushes. Orthodontic Plaque Index (OPI) was used as plaque index in this research. Analysis of data was using T-test. Results: Pretest and posttest plaque index of conventional toothbrush were 70,94 and 40,20. Pretest and posttest plaque index of orthodontic toothbrush were 65,59 and 23,74. The average difference in pretest and posttest plaque index of conventional toothbrush was 30,74 and orthodontic toothbrush was 41,84. The result was tested by using independent t-test and produced a significant value (P value) of 0,001 Conclusion: The use of orthodontic toothbrush with Charter method is more effective than conventional toothbrush in removing plaque. Keywords: Plaque index, conventional toothbrush, orthodontic toothbrush